Metal levels of canned fish sold in Türkiye: health risk assessment - Kosker, Ali Riza; Gundogdu, Sedat; Esatbeyoglu, Tuba; Ayas, Deniz; Ozogul, Fatih (Frontiers in Nutrition, 2023)
This study analyzed 34 canned fish products, including 28 tuna specimens, 3 salmon specimens, 1 mackerel specimen, and 1 anchovy specimen, from 13 different brands purchased in Türkiye. The study aimed to determine metal/metalloid levels in canned fish and potential health risks for both children and adult consumers. The metal/metalloid levels in the samples were determined using an Inductively Coupled Plasma-Mass Spectrometer (ICP-MS), with the range of levels found as follows (mg/kg, ww): Fe (12.12-101.4), , Zn (4.06-33.56), Se (0.24-10.74), Al (1.41-14.45), Cr (0.06-4.08), Pb (0.10-0.43), Cd (0.001-0.110), and As (0.01-0.13). Estimated weekly intake (EWI) levels were found that the consumption of canned fish products did not pose any risk based on the EWI levels and provisional tolerable weekly intake (PTWI) limits. However, three tuna samples had target hazard quotient (THQ) levels above the threshold (>1). Arsenic levels were found to increase the carcinogenic risk for child consumers if they heavily consumed 18 canned fish products, including 15 tuna, 2 salmon, and 1 mackerel. The maximum allowable consumption rates (CRmm) for each canned fish product were calculated monthly. Consequently, the consumption of canned fish by children can pose health risks.